Socio-behavioral factors influence prevalence and severity of dental caries in children with primary dentition - Borges, Heloisa Carvalho [UNESP] (2012)
The aim of this study was to analyze the influence of sociobehavioral variables on the prevalence and severity of dental caries in 4-to 6-year-old children. A cross-sectional study was performed on a sample of 1993 children enrolled in 58 public preschools from Araçatuba City, São Paulo State, Brazil, during 2010. The exams were made using the decayed, missing, and filled teeth index (World Health Organization methodology) and detection criteria for non-cavitated lesions. A tested, self-administered questionnaire was sent to parents to obtain information about their socio-behavioral characteristics. Standardization was performed to verify concordance among examiners (kappa = 0.84). The prevalence of cavitated caries lesions was 41.2% (821), and the prevalence of both, cavitated and non-cavitated caries lesions, was 43.9% (875). The means ± standard deviations of the decayed, missing, and filled teeth index for children aged 4, 5, and 6 years were 1.18 ± 2.45, 1.65 ± 2.67, and 1.73 ± 2.77, respectively. Caries were significantly more prevalent in children from families with low incomes and low educational levels. The presence of dental caries was associated with access to dental services (p < 0.05). The associations between both, cavitated and non-cavitated dental caries lesions, and the frequency of oral hygiene were statistically significant. The prevalence of dental caries in preschoolers was strongly associated with factors related to the children's parents. Therefore, information about parents' socio-economic status, behaviors, and attitudes in relation to oral health should be considered when planning prevention and educational programs for the oral health of preschool children.